FEMINISME DALAM SERIAL GADIS KRETEK KARYA RATIH KUMALA - Ananto, Irfan; Fatimah; Yolanda (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research aims to understand exactly what feminism is in the series. The data in this research includes a scene/dialogue in the series in it. This research uses content analysis techniques, by collecting data through watching, listening, note-taking and data identification techniques. The research results in the Kretek Girl series cover economic, political and social life. A total of 60 data have been found in total. Economic life has 10 data, political life has 28 data and social life has 22 data. So it can be concluded that the feminism contained in the Kretek Girl series is more dominant in political life. Based on the research above, the implication is that feminism continues to fight for women's rights, including the right to hold political office, work, fair wages, equal wages, and eliminate the gender wage gap and women, to receive education, have the same rights as men.